Design and Development of Novel Herbal Suppository Formulation for Prostatitis Treatment - Golembiovska, Olena; Dmytrenko, Oleksandra; Galkin, Alexander (Innovative Biosystems and Bioengineering, 2024)
Background. Prostatitis is a common inflammatory condition of the prostate gland, often treated with antibiotics and anti-inflammatory drugs, which may have limited efficacy and side effects. Herbal therapies offer a promising alternative due to their natural anti-inflammatory properties. Objective. This study aims to design, develop, and evaluate physicochemical, biopharmaceutical and microbiological properties of novel herbal suppository formulations for the treatment of prostatitis, optimizing their biopharmaceutical profiles. Methods. Excipients were selected to form suppositories with herbal ingredients known for their anti-inflammatory effects, specifically lovage, saw palmetto, and calendula CO2 extracts. The formulations were assessed based on key quality parameters, including organoleptic characteristics, average mass, melting point, deformation time, disintegration time, microbiological purity, and pH, ensuring compliance with European Pharmacopoeia (Ph. Eur.) standards. Biopharmaceutical studies compared the release profiles of active compounds from different suppository bases. Results. Suppositories based on Witepsol® H15 exhibited satisfactory organoleptic properties, appropriate melting points, and acceptable deformation and disintegration times. The pH levels were within the required range, and microbiological tests confirmed purity. Biopharmaceutical evaluations showed that Witepsol® H15 suppositories had the most appropriate release rates of active compounds compared to those made with other bases. Conclusions. The novel herbal suppositories developed in this study show promise for managing prostatitis based on preliminary evaluations of their physicochemical, microbiological, and biopharmaceutical properties. Further clinical studies are required to confirm their efficacy and safety.